2006
DOI: 10.1158/1078-0432.ccr-06-0162
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Growth and Metastasis of Mouse Mammary Carcinoma by Selective Inhibitor of Transforming Growth Factor-β Type I Receptor KinaseIn vivo

Abstract: Purpose: Transforming growth factor-h (TGF-h) suppresses tumor development by inhibiting cellular proliferation, inducing differentiation and apoptosis, and maintaining genomic integrity. However, once tumor cells escape from the tumor-suppressive effects of TGF-h, they often constitutively overexpress and activateTGF-h, which may promote tumor progression by enhancing invasion, metastasis, and angiogenesis and by suppressing antitumor immunity. The purpose of this study was to test this hypothesis usingTGF-h … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
92
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 77 publications
14
92
3
1
Order By: Relevance
“…TGFβ (100 pM) activates Smad2 and Smad3 with an expected early response peaking at 2 hr. The selective TβRI kinase inhibitor, SD208, which inhibits the phosphorylation/activation of Smad2 and Smad3, 62 obviated TGFβ-mediated growth inhi bition. Smad2 and Smad3 elicit Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ (100 pM) activates Smad2 and Smad3 with an expected early response peaking at 2 hr. The selective TβRI kinase inhibitor, SD208, which inhibits the phosphorylation/activation of Smad2 and Smad3, 62 obviated TGFβ-mediated growth inhi bition. Smad2 and Smad3 elicit Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds often compete with binding of ATP to the ATP-binding site of the kinase, and several of them inhibit the TbRI kinase selectively, but often also inhibit the activin type I receptor ALK-4 and the nodal type I receptor ALK-7 (Yingling et al 2004). TbRI kinase inhibitors have been shown, in animal models, to inhibit invasion and metastasis of, for example, breast cancer cells (Bandyopadhyay et al 2006;Ge et al 2006;Ehata et al 2007;Liu et al 2012), melanoma cells (Mohammad et al 2011), glioma cells (Uhl et al 2004;Zhang et al 2011), and mesothelioma cells (Suzuki et al 2007). The effect of the inhibitors include inhibition of mesenchymal transition of the tumor cells, activation of the immune system, inhibition of angiogenesis, inhibition of osteolysis preventing bone metastasis, and normalization of tumor stroma.…”
Section: Tgf-b Family Receptorsmentioning
confidence: 99%
“…(14) For example, SB-431542, SD-208 and SM16 are small molecules that block the catalytic activity of TbRI and have been reported to be potent antitumor or antimetastatic agents. (15)(16)(17) It has also been reported that neutralizing antibody against TGF-b ligand has a suppressive effect on lung metastasis, (18) and that a Smad-binding peptide aptamer inhibits TGF-b signalling and EMT. (19) To determine whether the targeting of ALK5 offers an effective therapeutic approach to the suppression of breast cancer metastasis, we examined the effects of the novel ALK5 inhibitor EW-7203 (3-((5-( [1,2,4]triazolo [1,5-a]pyridin-6-yl)-4-(6-methylpyridin-2-yl)thiazol-2-ylamino)methyl)benzonitrile) on motility, Smad signalling and EMT in NMuMG and MCF10A cells in vitro and on the development of metastasis in vivo using an orthotopic xenograft model.…”
mentioning
confidence: 99%